2019
DOI: 10.1101/571802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active Efficient Coding Explains the Development of Binocular Vision and its Failure in Amblyopia

Abstract: The development of vision during the first months of life is an active process that comprises the learning of appropriate neural representations and the learning of accurate eye movements. While it has long been suspected that the two learning processes are coupled, there is still no widely accepted theoretical framework describing this joint development. Here we propose a computational model of the development of active binocular vision to fill this gap. The model is based on a new formulation of the Active E… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Specific to exploration speed, it is shown that when participants were asked to haptically discriminate spatial frequencies of gratings, low performing participants could improve their performance by adjusting the scanning velocity to the one used by better performing participants (Gamzu & Ahissar, 2001). In fact, the statistics of the sensory input are shaped by exploratory behavior, which therefore may contribute to efficient encoding, consistent with the recently proposed "active efficient coding" theory (Eckmann et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Specific to exploration speed, it is shown that when participants were asked to haptically discriminate spatial frequencies of gratings, low performing participants could improve their performance by adjusting the scanning velocity to the one used by better performing participants (Gamzu & Ahissar, 2001). In fact, the statistics of the sensory input are shaped by exploratory behavior, which therefore may contribute to efficient encoding, consistent with the recently proposed "active efficient coding" theory (Eckmann et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Receptive field properties in the early visual pathway (Atick & Redlich, 1992; Olshausen & Field, 1996;1997) as well as the tuning properties of auditory nerve fibers (Lewicki, 2002; Smith & Lewicki, 2006) can emerge by efficiently encoding natural images or sounds respectively. Recently, it was shown that efficient coding could also explain the simultaneous development of vergence and accommodation as a result of maximizing coding efficiency of the retinal signals (Eckmann, Klimmasch, Shi, & Triesch, 2020). There is currently a lot of interest whether higher level representations can also be learned by efficient encoding of the retinal images (Fleming & Storrs, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In search for such principles, we take inspiration from the organism’s limited energy budget. Expanding on previous work on efficient coding and sparse coding (Barlow et al, 1961; Bell and Sejnowski, 1995; Olshausen and Field, 1996; Bialek et al, 2006; Berkes and Wiskott, 2005; Chalk et al, 2018; Eckmann et al, 2020), we subject recurrent neural networks (RNNs) to predictable sequences of visual input and optimise their synaptic weights to minimise what constitutes the largest source of energy consumption in biological systems: action potential generation and synaptic transmission (Sengupta et al, 2010). We then test the resulting networks for phenomena typically associated with predictive coding.…”
Section: Introductionmentioning
confidence: 99%
“…Our model is based on the Active Efficient Coding (AEC) framework, an extension of classic efficient coding ideas [ 14 , 15 ] to active perception. Previous AEC models have been restricted to the visual domain, where they have explained the self-calibration of active binocular vision, active motion vision, the control of accommodation and torsional eye movements and combinations thereof [ 16 , 17 , 28 , 29 ]. Moreover, AEC models have been developed to learn eye hand coordination tasks such as autonomous tracking of a robot arm [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%